2020
DOI: 10.1111/jfbc.13367
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of duck egg white and insight into the biological functions of identified phosphoproteins

Abstract: Posttranslational modifications (PTMs) have been found in food proteins, primarily in glycosylated and phosphorylated forms. Among all PTMs, reversible phosphorylation of proteins at serine (S), threonine (T), and tyrosine (Y) residues is one of the most important and pleiotropic modifications (Qi et al., 2015). Phosphorylation plays a vital role in controlling protein functions and cell signaling through conformational changes in proteins (Ya, 2002). A previous report found that the phosphorylation of food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…According to reports, compared to other avian egg yolks, duck egg yolks have unique benefits in terms of nutrition, bioactivities, and processing [12,13]. Proteomic analysis of different poultry eggs and the identification of their biological activities have been published [14,15]. Using a comparative proteomic approach, only a small number of distinct proteins have been detected in the yolks of chicken, duck, and quail eggs [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to reports, compared to other avian egg yolks, duck egg yolks have unique benefits in terms of nutrition, bioactivities, and processing [12,13]. Proteomic analysis of different poultry eggs and the identification of their biological activities have been published [14,15]. Using a comparative proteomic approach, only a small number of distinct proteins have been detected in the yolks of chicken, duck, and quail eggs [15].…”
Section: Introductionmentioning
confidence: 99%
“…The proteomic analysis of different avian eggs and the bioactivity of the identified proteins have been published. 16,21 Despite the importance of protein phosphorylation in enhancing the functional characteristics of egg proteins, the DEY phosphoproteome analysis is largely unknown. The present work attempted to provide an in-depth phosphoproteomic analysis of DEY using high-resolution liquid chromatograph-mass spectrometer/ mass spectrometer (LC-MS/MS) combined with an immobilized metal affinity chromatography (IMAC) enrichment strategy and compared with CEY (Geng F, 2021, unpublished data) for revealing species diversity in terms of bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous proteomic study revealed that phosphorylation also plays a significant regulatory role in chicken embryonic development 15 . Recently, we identified 36 phosphoproteins in duck egg white, which were mostly involved in the binding, transport activity, biological regulation, and metabolic processes 16 . Phosphorylation supposedly plays a potential role in enhancing the biological functions of duck egg white proteins, such as metabolic activity, antibacterial and antiviral activity, and antioxidant ability 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations